2018
DOI: 10.1002/anie.201803907
|View full text |Cite
|
Sign up to set email alerts
|

Cofactor Biogenesis in Cysteamine Dioxygenase: C−F Bond Cleavage with Genetically Incorporated Unnatural Tyrosine

Abstract: Cysteamine dioxygenase (ADO) is a thiol dioxygenase whose study has been stagnated by the ambiguity as to whether or not it possesses an anticipated protein-derived cofactor. Reported herein is the discovery and elucidation of a Cys-Tyr cofactor in human ADO, crosslinked between Cys220 and Tyr222 through a thioether (C-S) bond. By genetically incorporating an unnatural amino acid, 3,5-difluoro-tyrosine (F -Tyr), specifically into Tyr222 of human ADO, an autocatalytic oxidative carbon-fluorine bond activation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(47 citation statements)
references
References 23 publications
1
46
0
Order By: Relevance
“…S8). Under the conditions tested therefore the unusual posttranslational modification observed to enhance turnover in mammalian CDOs was not identified in the AtPCOs, though we cannot rule out that a cross-link may be observable using different techniques (31).…”
Section: Resultsmentioning
confidence: 82%
See 2 more Smart Citations
“…S8). Under the conditions tested therefore the unusual posttranslational modification observed to enhance turnover in mammalian CDOs was not identified in the AtPCOs, though we cannot rule out that a cross-link may be observable using different techniques (31).…”
Section: Resultsmentioning
confidence: 82%
“…This suggests that PCO enzymes cannot form an equivalent thioether cross-link; however, residues elsewhere in the AtPCO active sites do have the potential to form a similar posttranslational modification. Thioether crosslink formation has been observed in the active site of human cysteamine dioxygenase, HsADO, between Cys220 and Tyr222 (13,31). HsADO is a thiol dioxygenase which also catalyses oxidation of protein N-terminal cysteine residues and retains Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is plausible that the other thiol dioxygenases exhibit similar substrate-bound structures, although they have not yet been characterized by XRD. 23, 5…”
Section: Introductionmentioning
confidence: 99%
“…Indeed as for CDO, iron coordination is needed for ADO activity and when iron binding was ablated using a His to Ala variant cysteamine dioxygenase activity was lost [35]. It is also possible that ADO shares another structural feature with CDO: in 2018, Wang et al published evidence that a Cys-Tyr crosslink can occur in ADO between Cys 220 and Tyr 222 [37]. Interestingly, recent spectroscopic investigations indicate that metal -substrate coordination in ADO is distinctive from that of CDO: While crystallographic evidence has shown these enzymes to bind their substrates in a bidentate manner, spectroscopic evidence has indicated that ADO binds cysteamine in a monodentate manner via the thiol but not via its amine group [38,39].…”
Section: Cysteamine Dioxygenasementioning
confidence: 99%